Application of Quantitative Feedback Theory to the Robust Control of a Coaxial Micro-helicopter - Meksi, Aissa; Boudinar, Ahmed Hamida; Kouadri, Benatman (Engineering Research: Perspectives on Recent Advances Vol. 1, 2024)
Unmanned aerial vehicles (UAVs) are aircraft capable of flying and performing a mission without human presence on board. Initially developed as part of military activities, there is now a great potential for civil activities (surveillance, cartography...). This chapter on the dynamic analysis and QFT-based robust control design of a coaxial micro-helicopter is significant for the scientific community as it addresses a critical intersection of aerodynamics and control engineering. The paper presents the dynamic behavior of the micro-helicopter under Quantitative Feedback Theory (QFT) control, highlighting the non-linear and complex flight dynamics of autonomous air vehicles (AAVs) with rotating rings. It emphasizes the necessity of characterizing these non-linearities for each flight configuration to enable effective autonomous flight and navigation capabilities. To tackle this complexity, the nonlinear model is linearized around an operating point using specific assumptions, followed by the application of a robust QFT control law to meet performance specifications. QFT serves as a powerful design method that leverages frequency domain concepts to manage uncertainties commonly encountered in small aerial vehicle design. The QFT design approach involves conventional frequency response loop shaping, manipulating gain variables in conjunction with the poles and zeros of the nominal transfer function, with the entire process executed using MATLAB software. This research not only presents innovative methodologies that enhance stability and performance in increasingly complex environments but also lays a foundation for future studies in micro-robotics and autonomous systems, underscoring the importance of interdisciplinary collaboration. Personally, I appreciate the chapter for its clear articulation of theoretical concepts alongside practical applications, making it both accessible and highly relevant to ongoing discussions in the field. Overall, the integration of theory and practice in this work contributes valuable insights to both academia and industry.